2013
DOI: 10.1590/0037-868216612013
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the usefulness of external support to immunization coverage in Guinea-Bissau: a Delphi analysis of the GAVI-Alliance cash-based support

Abstract: Introduction: Although many countries have improved vaccination coverage in recent years, some, including Guinea-Bissau, failed to meet expected targets. This paper tries to understand the main barriers to better vaccination coverage in the context of the GAVI-Alliance (The Global Alliance for Vaccines and Immunisation) cash-based support provided to Guinea-Bissau. Methods:The analysis is based on a document analysis and a three round Delphi study with a final consensus meeting. Results: Consensus attributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The lack of human resources, resulting in incomplete technical Cad. Saúde Pública 2023; 39(1):e00102922 teams and the closure of health centers nationwide, is a major obstacle 36 . However, our data show that maternal schooling level is a key factor that facilitates access to immunization.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of human resources, resulting in incomplete technical Cad. Saúde Pública 2023; 39(1):e00102922 teams and the closure of health centers nationwide, is a major obstacle 36 . However, our data show that maternal schooling level is a key factor that facilitates access to immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Weight coe cients for primary, secondary, and tertiary indicators were derived from the matrix analysis results, using the index weight coe cient to evaluate the signi cance of each indicator. MATLAB 2016a was employed to input the experts' assessments of rst-level indicators and establish a matrix for acquiring and organizing weight coe cients, maximum eigenvalues (λ max), consistency index (CI), and random consistency ratio (CR) [32]. A consistency assessment was conducted using the computed values, and a CR value below 0.1 indicated a successful outcome.…”
Section: Ahp Weight Assessmentmentioning
confidence: 99%
“…In most of sub-Saharan Africa, access to health care services by nomads is poor compared to settled populations, and there is no satisfactory strategy devised yet to deliver proper health care to remote populations. Disease control programmes also often fail to reach migratory populations [4][5][6][7] . For example, a study among the settled and nomadic Rendille in Kenya revealed that all children >12 months of age in Korr village had full immunisation coverage, while among their nomadic counterparts immunisation coverage was 0% 8 .…”
Section: More Than 60% Of the Nomads And Semi-nomads In The Worldmentioning
confidence: 99%